Design and Synthesis of 68Ga‐Labeled Peptide‐Based Heterodimers for Dual Targeting of NTS1 and GRPR - Bodin, Sacha; Previti, Santo; Jestin, Emmanuelle; Rémond, Emmanuelle; Vimont, Delphine; Lamare, Frédéric; Ait‐Arsa, Imade; Hindié, Elif; Cavelier, Florine; Morgat, Clément (ChemMedChem, 2025)
Tumor heterogeneity remains one of the main obstacles for cancer diagnosis and treatment. The simultaneous targeting of several cancer biomarkers is an appealing approach for improved diagnostic procedures. Neurotensin receptor 1 (NTS1) and Gastrin‐Releasing Peptide Receptor (GRPR) are both G‐protein coupled receptors with complementary profile of expression in several cancer types. This work proposes the design, the synthesis and the in vitro radiopharmaceutical characterization of three heterodimers, based on GRP/NT modified peptides, radiolabeled with gallium‐68. Two NTS1/GRPR targeting pharmacophores containing linear hybrids that differ in the C‐terminus were synthesized (i. e., JMV 7110 and JMV 7253). The branched analogue of the silicon‐containing heterodimer JMV 7110, namely JMV 7266, was also synthesized. After radiolabeling with 68Ga, saturation binding studies performed on HT29 (NTS1+/GRPR−) and PC3 (NTS1+/GRPR+) cells demonstrated a significant loss in NTS1 and GRPR affinity compared to the reference monomers with the exception of the NTS1 affinity of [68Ga]Ga‐JMV 7266 which was preserved. Considering cellular processing, NTS1‐internalization at 1 h was the highest with [68Ga]Ga‐JMV 7266 and was similar to the reference compound. Interestingly [68Ga]Ga‐JMV 7266 demonstrated lower efflux than the other linear heterodimers but also than its NT reference compound. The branched structure of [68Ga]Ga‐JMV 7266 seems beneficial for dual NTS1/GRPR targeting. Tumor heterogeneity is challenging for cancer diagnosis and treatment. This study designs and evaluates three gallium‐68 radiolabeled heterodimers targeting two G‐protein coupled receptors, namely NTS1 (neurotensin receptor 1) and GRPR (gastrin‐releasing‐peptide receptor). The branched analogue [68Ga]Ga‐JMV 7266 preserves NTS1 affinity, exhibits higher internalization and reduced efflux, highlighting its potential as a promising dual‐targeting agent for improved cancer imaging.